STUDI KUALITATIF INTEGRASI PEMBERDAYAAN EKONOMI KELUARGA DALAM PEMBELAJARAN IPS DI PACITAN - M. Fashihullisan; Ahmad Hariyadi; Caraka Yoga Aprilya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Contextual learning is an important aspect of Social Studies (IPS) education. One important element of contextual Social Studies learning is family economic empowerment. This study aims to analyze the integration of family economic empowerment into Social Studies learning in an elementary school in Pacitan Regency, Indonesia. This study employed a qualitative descriptive approach, with data collected through in-depth interviews with a Social Studies teacher, classroom observations, and analysis of relevant documents and learning materials. Informants were selected using purposive sampling, and the data were analyzed through triangulation techniques. The findings indicate that family economic empowerment has not yet been integrated into Social Studies learning at the elementary school level in Pacitan. Family economic empowerment should be integrated into Social Studies learning through contextual learning, project-based learning, and the utilization of family economic potential as a learning resource. The main challenge to integrating family economic empowerment into Social Studies learning is teachers' limited competence in developing learning materials and curriculum.